2021
DOI: 10.1007/s11136-021-02797-2
|View full text |Cite
|
Sign up to set email alerts
|

Health-promoting behaviors mediate the relationship between eHealth literacy and health-related quality of life among Chinese older adults: a cross-sectional study

Abstract: Purpose The aim of this study was to examine the association between eHealth literacy and health-related quality of life (HRQoL) and explore whether health-promoting behaviors mediate the association between eHealth literacy and HRQoL among Chinese older adults. Methods An anonymous cross-sectional survey was conducted among 2300 adults aged 60 or older from Jinan, China. The eHealth Literacy Scale, Short-Form Health-Promoting Lifestyle Profile, and Short-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 45 publications
3
25
0
Order By: Relevance
“…Among all the indicators on health, quality of life is considered as a multi-dimensional and comprehensive indicator that better reflect well-being, which is affected by physical, psychological, and social factors (2,3). Numerous studies had explored age, residence, income level, lifestyle factors, chronic disease, and social health status as factors associated with quality of life (2,(4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among all the indicators on health, quality of life is considered as a multi-dimensional and comprehensive indicator that better reflect well-being, which is affected by physical, psychological, and social factors (2,3). Numerous studies had explored age, residence, income level, lifestyle factors, chronic disease, and social health status as factors associated with quality of life (2,(4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Literature had reported the potential factors associated with poor quality of life in the general population or patients in China (3,8,11,12). Zhang et al (12) found that the prevalence and decline in quality of life of multimorbid olderaged people were severe in Shandong province, China.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, among the niche themes, specific topics such as “quality of life” and “public health” have arisen as central ones in addressing public policies [ 89 , 90 ]. Even if still understudied, the presence of these two keywords confirm that scholars are moving towards new methodologies for addressing complex issues (such as CVD) thanks to “old” implementation strategies (PASA) in “new” pathways (m-health) [ 91 , 92 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the overall digital health literacy of community-dwelling older adults was relatively low. Previous research results showed that there was a gap between the digital health literacy level of Chinese older adults and that of developed countries [ 14 , 27 ]. One possible reason is that China gained full access to the Internet in 1994, later than many developed countries.…”
Section: Discussionmentioning
confidence: 99%
“…Digital health has become an important way to achieve the vision of health for all and has proven to be beneficial for both individuals and society [ 10 ]. From an individual perspective, digital health services help to increase public participation, promote better self-care behaviors and healthy lifestyles [ 11 , 12 ], and thus improving health outcomes [ 13 , 14 ]. From a socioeconomic perspective, the use of digital health can generate sustainable economic net benefits by providing better treatment for patients and improving the efficiency of patient management [ 15 ].…”
Section: Introductionmentioning
confidence: 99%